A STUDY ON THE EFFECT OF #RP612FIC TO GRADE 10 PUBLIC SCHOOL STUDENTS IN MANILA TOWARDS APPRECIATING PHILIPPINE HISTORY (2016) - Balahim, John Carl A.; Gloria, Ma. Joanna Erreevee O. and Rodriguez Angeline DC. 4 0 16; 5
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2016.;Bachelor of Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2